Easy preparation and characterization of conducting polymer-low molecular weight organogel system. (20th March 2015) - Kuwahara, Rie Yamazaki; Yamagishi, Hodaka; Hashimoto, Kumi; Tamesue, Shingo; Yamauchi, Takeshi; Tsubokawa, Norio
Abstract: Novel organogel system was successfully prepared from organically dispersed polyaniline (PANI) and a low molecular weight organogel system. Organogelator, consisting of cholesteryl hydrogen succinate (CHS) and 1, 10-diaminodecane, and organically well-dispersible PANI were synthesized. PANI-containing toluene gels showed thermal reversibility and thixotropic behavior. Viscoelastic measurements demonstrated that PANI-containing toluene gels show rapid and repeated thixotropic behavior. A ballpoint pen refill was packed with PANI-containing toluene gel just like a gel ink, lines similar to the ones produced by ballpoint pen were successfully produced. In addition, PANI-organogelator composites of arbitrary shape were easily prepared by means of toluene evaporation from toluene gel. "Dried" PANI composites showed electrical conductivity. Compared with the neat PANI, the electrical conductivity of the PANI-organogelator composite is hardly affected by about 10 weight% of organogelator in the composite. Graphical abstract: